Imperfections in perfect architecture: The orb web of spiders - Alain PASQUET; Julia MARCHAL; Mylène ANOTAUX; Raymond LEBORGNE (European Journal of Entomology, 2013)
Among animal constructions, the orb webs of spiders are perfect geometrical architectural models. Webs are constructed by means of a succession of behaviours, which are often considered as instinctive and stereotyped. Anomalies in web structure are considered to be a consequence of variability in behaviour. In order to assess the variability in web structure, the spider Zygiella x-notata was allowed to build webs in the laboratory under standardized conditions. Webs (n = 127) were examined for anomalies, which were defined as modifications in the geometrical structure. Ten anomalies in the structure of webs produced by females, aged from 16 to 21 days after their adult moult, are described. The frequency of anomalies per web varies from 5 to 98. A very low percentage of the spiral elements of a web (less than 5%) were affected. Anomalies in the radii were less numerous (mean = 3 ± 3) than those in the sticky spiral (mean = 21 ± 11). Anomalies in the sticky spiral were different and more frequent in the peripheral than central parts of the webs. They were also relatively more numerous in the upper than in the lower part of the webs. Total number of anomalies was positively correlated with particular web characteristics (capture area, length of capture thread, width of the lower part of the web and mean distance between two spiral turns in the lower part) but not to the physical characteristics of the spiders (mass and size). Our results indicate that the orb webs of spiders, which are considered to be perfect geometrical structures, include anomalies mainly in the structure of the sticky spiral. These anomalies were the result of variability in behaviour during web building. In conclusion, their identification and description enable one to use them in spider webs as an index of behavioural variability.